2001
DOI: 10.1002/sia.1079
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary segregation and fracture resistance of engineering steels

Abstract: The developments in surface analytical techniques and experimental measurements have made it possible to understand grain boundary segregation processes and related fracture mechanisms. This article shows how experimental contributions have led to the concept of grain boundary segregation isotherms for a complete understanding of grain boundary segregation behavior, and its effect on material properties in terms of the kinetics of segregation, the interaction processes amongst trace and solute elements and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The concentration ratio of Ni to Sn at the grain boundary was constant and equal to about 1.1 [57] . Misra could not interpret such experimental results completely.…”
Section: Non-equilibrium Grain Boundary Cosegregation (Ngcs)mentioning
confidence: 98%
See 1 more Smart Citation
“…The concentration ratio of Ni to Sn at the grain boundary was constant and equal to about 1.1 [57] . Misra could not interpret such experimental results completely.…”
Section: Non-equilibrium Grain Boundary Cosegregation (Ngcs)mentioning
confidence: 98%
“…2.6NiCrMoV steel was first solution treated for 1 h at 1223 K, water quenched, and then aged in the range 700-900 K. Misra [57] measured the grain boundary composition of such treated samples with AES, and found that the grain-boundary concentrations of both Sn and Ni first increased to reach a maximum and then decreased with further increasing ageing time. The concentration ratio of Ni to Sn at the grain boundary was constant and equal to about 1.1 [57] .…”
Section: Non-equilibrium Grain Boundary Cosegregation (Ngcs)mentioning
confidence: 99%
“…Environmental effects such as hydrogen can also embrittle the interfaces [430,431]. Although we have come a long way towards experimental characterization of chemically complex interfaces under stress [281,[432][433][434][435][436], atomistic calculations [437][438][439], especially by first-principles methods which can handle the complex interfacial chemistry, are invaluable for providing energetic information (Section 5.3).…”
Section: Interfaces and Fracturementioning
confidence: 99%
“…Among different pairs of cosegregating elements, the cosegregation of Cr and N has been paid much attention by researchers, [18][19][20][21][22][23][24][25][26][27] even when found in a Ni-based alloy. [28] In References 21 through 23, Misra et al have demonstrated the cosegregation of Cr and N using the isotherms, but have not elucidated whether the cosegregation is equilibrium or nonequilibrium.…”
Section: Introductionmentioning
confidence: 99%